KOLABORASI PEMERINTAHAN KABUPATEN TANAH DATAR DALAM PEMULIHAN PARIWISATA PASCA PANDEMI TAHUN 2021-2022 - Halim Arrazak; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Covid-19 pandemic that hit Indonesia left a number of homework to be completed by the government. One of the real impacts is the decrease in the number of tourists in Indonesia which affects the smooth running of the community's economy. One area that has experienced a drastic decrease in the number of tourists is Tanah Datar District. To overcome the problems that occurred, the Tanah Datar Regency Government and the Kenagarian Government agreed to collaborate in tourism recovery. The collaboration that was carried out resulted in a collaborative policy called "Satu Nagari Satu Event". Apart from aiming to restore tourism in Tanah Datar Regency, the collaboration that is being carried out also aims to preserve culture in Tanah Datar Regency. This study uses collaboration theory by Kirk Emerson. In this theory the quality of collaboration can be measured through three stages: collaboration dynamics, collaborative actions, and the impact of collaboration adaptation. The approach used in this study is a qualitative approach. This type of research is descriptive. The research location is in Tanah Datar Regency, to be precise at the Tourism, Youth and Sports and Nagari Office which implements the â€œSatu Nagari Satu Eventâ€ policy. The type of data in this research is divided into primary data using purposive sampling technique of informant data collection and secondary data in the form of supporting documents. The results of this study can be seen after making a comparison between the collaboration process carried out by the Tanah Datar District Government and the Kenagarian Government with the quality and stages of collaboration theory by Kirk Emerson. The results of the collaboration carried out have a significant influence on the development of tourism in Tanah Datar Regency. This is marked by an increase in the number of tourists, the preservation of culture in the village, the recovery of the MSME sector, and the growth of the village's independence in exploiting tourism potential. Keywords : Collaborative Dynamics, Collaborative Actions, Impact and Adaptation